Placental Growth Factor in Bladder Cancer Compared to the Diagnostic Accuracy and Prognostic Performance of Vascular Endothelial Growth Factor A - Soukup, Viktor; Čapoun, Otakar; Pešl, Michael; Sobotka, Roman; Vávřová, Lucie; Hanuš, Tomáš; Zima, Tomáš; Kalousová, Marta (Anticancer research, 2018)
BACKGROUND/AIM: To evaluate the diagnostic accuracy and prognostic performance of urinary and plasma levels of placental growth factor (PLGF) and provide their comparison with the results of vascular endothelial growth factor A (VEGF-A) in patients with primary and recurrent urinary bladder cancer. MATERIALS AND METHODS: The enzyme-linked immunosorbent assay (ELISA) was used to assess urinary and plasma concentrations of PLGF and VEGF-A in 240 individuals. RESULTS: PLGF levels in urine and plasma were significantly higher in patients with primary bladder cancer than in healthy individuals (p=0.003, p=0.005, respectively). Area under the curve (AUC) of urinary PLGF was 0.68; AUC of plasma PLGF levels was 0.65. Patients with the urine levels of PLGF higher than 82.33 pg/ml had three times higher risk of recurrence. In patients with recurrent bladder cancer, the urinary concentrations of PLGF did not significantly differ from the concentrations in patients without current disease (p=0.61). However, plasma PLGF levels were significantly higher in patients diagnosed with tumor recurrence (p=0.001); AUC of plasma PLGF levels was 0.69. Moreover, patients with plasma levels higher than 10.09 pg/ml had a five-times higher risk of future tumor recurrence. The diagnostic accuracy of PLGF was comparable with VEGF-A. CONCLUSION: From a clinical point of view, PLGF could be considered a valid diagnostic test for the detection of primary and recurrent bladder cancer. In patients with recurrent bladder cancer, plasma PLGF levels can differentiate individuals at risk of tumor recurrence.
Keywords: Neoplasm Recurrence, Local; prognóza; vaskulární endoteliální růstový faktor A; Prognosis; Placenta Growth Factor; lidé; Urinary Bladder Neoplasms; Vascular Endothelial Growth Factor A; placentární růstový faktor; nádory močového měchýře; lokální recidiva nádoru; Humans